2016
DOI: 10.3746/jkfn.2016.45.6.918
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Proliferative Activities of Oats under Different Solvent Extraction Conditions

Abstract: The objective of this study was to determine the antioxidant and anti-proliferative activities of methanol, ethanol, acetone, and ethyl acetate extracts from oats (Avena sativa L.). Total polyphenol contents of extracts were analyzed by Folin-Ciocalteu assay. The antioxidant activities of extracts were determined by 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activities and reducing power. The anti-proliferative activities of colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It was observed that the total polyphenol content, scavenging of ABTS and DPPH radicals, and reducing power were the greatest in methanol extracts [ 118 ]. In addition, methanol extracts had the most significant inhibitory effects on the proliferation of colorectal cancer (HCT116), lung cancer (NCI-H460), and breast cancer (MCF7) cells [ 119 ]. Although there were differences in the antioxidant effects and inhibition of cancer cell proliferation of oats depending on the extraction solvent, these findings demonstrate that oats have antioxidant and anti-cancer effects [ 98 , 120 ].…”
Section: Other Bioactive Ingredients and Functionalitiesmentioning
confidence: 99%
“…It was observed that the total polyphenol content, scavenging of ABTS and DPPH radicals, and reducing power were the greatest in methanol extracts [ 118 ]. In addition, methanol extracts had the most significant inhibitory effects on the proliferation of colorectal cancer (HCT116), lung cancer (NCI-H460), and breast cancer (MCF7) cells [ 119 ]. Although there were differences in the antioxidant effects and inhibition of cancer cell proliferation of oats depending on the extraction solvent, these findings demonstrate that oats have antioxidant and anti-cancer effects [ 98 , 120 ].…”
Section: Other Bioactive Ingredients and Functionalitiesmentioning
confidence: 99%